THERMO-ECONOMICIAL OPTIMIZATION OF GROUND SOURCE HEAT PUMP WITH HORIZONTAL GROUND HEAT EXCHANGERS FOR A HEATING SEASON IN ISTANBUL: A CASE STUDY - Demir, Hakan; Gonul, Alisan; Kayaci, Nurullah; Atayilmaz, S. Ozgur; Agra, Ozden (AMER SOC MECHANICAL ENGINEERS, 2014)
A ground-source heat pump (GSHP) system has three major components: a heat pump, an earth connection and an interior heating or cooling distribution system. The most important part of a ground source heat pump (GSHP) is the ground heat exchanger (GHE) that consists of pipes buried in the soil and is used for transferring heat between the soil and evaporator of the ground source heat pump. There are plenty of works on ground source heat pumps and ground heat exchangers in the literature. Most of the works on ground heat exchangers are based on the heat transfer in the soil and temperature distribution around the coil. Some of the works for thermo-economic optimization of thermal systems are based on thermodynamic cycles. In this paper, it was carried out that the thermo-economic optimization of a ground source heat pump system with horizontal ground heat exchangers operating in heating mode in Istanbul in Turkey. The monthly heat loads of a villa for every heating months were worked out by using TS825 (R) program. Also, average soil temperature has been calculated according to soil surface temperatures taken from Turkish State Meteorological Service belonging to last ten years. An objective function was defined based on heating capacity, initial investment and operating costs of ground source heat pump (GSHP). Then, the effects of the soil thermal conductivity, burial depth and variation of soil temperature on the objective function were investigated. Also, variation of COP value was carried out for burial depth and different condensation temperatures monthly.
Keywords: THERMOECONOMIC OPTIMIZATION; BURIED PIPE; SYSTEM; PERFORMANCE; Engineering